An aid to houseman interns by Prof. C. L. Bhattachan - Khakurel, Mahesh (Journal of Institute of Medicine Nepal, 2010)
The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 48